School Health is Public Health - Virginia J Noland; Catherine Troxler; Anna M. Torrens Salemi (University of North Florida, 2004)
This paper examines the school as a microcosm of public health practice. The history of school health is reviewed and key events leading to modern school health practice are identified. The school is presented as a community and a learning environment in which essential public health services are delivered. Examples of contributions of the Florida Department of Health and the Florida Department of Education to the health and well-being of Florida's children are presented briefly.